2022
DOI: 10.1007/s12633-021-01617-z
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Modeling of Sensitivity Parameters Influenced by Practically Feasible Arrangement of Bio-Molecules in Dielectric Modulated FET Biosensor

Abstract: In this paper, analytical modeling of a Dielectric Modulated Double Gate Field Effect Transistor (DM-DGFET) for biosensing application is presented with extensive data analysis. Firstly, the size of the nanogaps and arrangements of biomolecules in those gaps are optimized with respect to the sensitivity of the above sensor. The optimized DM-DGFET is next analyzed on the basis of its modeling and simulation. This paper addresses novel issues arising from arrangements of biomolecules, especially from practical p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…It is observed that in between four step patterns, the decreasing pattern shows almost 17%-21% higher sensitivity compared to other patterns. Table 1 shows the Comparative study of V th and on current sensitivity of AJDMDG MOSFET biosensor and DGFET based bionsensor [42]. As shown in table 1, the sensitivity of the biosensor is higher in decreasing patterns compared to the other patterns, and AJDMDG MOSFET biosensor has better sensitivity in terms of threshold voltage and on current.…”
Section: Performance Evaluation Of the Proposed Biosensormentioning
confidence: 97%
See 3 more Smart Citations
“…It is observed that in between four step patterns, the decreasing pattern shows almost 17%-21% higher sensitivity compared to other patterns. Table 1 shows the Comparative study of V th and on current sensitivity of AJDMDG MOSFET biosensor and DGFET based bionsensor [42]. As shown in table 1, the sensitivity of the biosensor is higher in decreasing patterns compared to the other patterns, and AJDMDG MOSFET biosensor has better sensitivity in terms of threshold voltage and on current.…”
Section: Performance Evaluation Of the Proposed Biosensormentioning
confidence: 97%
“…Because of the steric hindrance effect, primarily immobilized biomolecules prevent additional biomolecule entrance [53,54]. As a result, in actuality, partially occupied nanogap holes must be considered since it is critical to existent the issues associated with a random and arbitrary arrangement of biomolecules [42]. However, in this part, numerous nonuniform step patterns of biomolecules within the area of the nanocavity have been studied, and the evaluation of sensitivity for diverse patterns is presented below.…”
Section: Performance Evaluation Of the Proposed Biosensormentioning
confidence: 99%
See 2 more Smart Citations
“…Model of drain current in subthreshold region is calculated by utilizing expressions of surface potential obtained in previous section 45 and can be expressed as, (35) www.nature.com/scientificreports/ For linear regime, three transistor modelling approach has been employed to calculate the drain current 46 . Both the subthreshold current and linear regime current have been equated at transition region for the continuity of the current.…”
Section: Drain Current Modellingmentioning
confidence: 99%